2009
DOI: 10.1177/0363546509335464
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Multidirectional Shoulder Instability in Athletes

Abstract: Arthroscopic methods can provide an effective treatment for symptomatic multidirectional instability in an athletic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 27 publications
0
48
0
1
Order By: Relevance
“…The recurrence rate in the studies was between 4.7% and 10%. 21,[23][24][25] Previous studies have shown that the number of suture hooks used during the operation could affect the result. In a study by Watch et al, 27 it was suggested that the use of fewer than four suture hooks could have been one of the reasons for failure.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate in the studies was between 4.7% and 10%. 21,[23][24][25] Previous studies have shown that the number of suture hooks used during the operation could affect the result. In a study by Watch et al, 27 it was suggested that the use of fewer than four suture hooks could have been one of the reasons for failure.…”
Section: Discussionmentioning
confidence: 99%
“…Only 8 13,18,19,23,25,27,29,33 of 24 studies, describing 271 patients, also reported in their population individuals who underwent previous shoulder surgery for the management of MDI. Previous surgical procedures were performed in 71 (26%) of them: open capsular shift in 3 (4%), 13 laser-assisted capsular shrinkage in 10 (14%), 18 diagnostic arthroscopy in 2 (3%), 19 thermal capsulorrhaphy in 2 (3%), 23 and Bankart repair in 4 (6%).…”
Section: Previous Surgerymentioning
confidence: 99%
“…Previous surgical procedures were performed in 71 (26%) of them: open capsular shift in 3 (4%), 13 laser-assisted capsular shrinkage in 10 (14%), 18 diagnostic arthroscopy in 2 (3%), 19 thermal capsulorrhaphy in 2 (3%), 23 and Bankart repair in 4 (6%). 25 In 50 (70%) patients, the previous surgery for instability was not specified.…”
Section: Previous Surgerymentioning
confidence: 99%
“…That is because they suffer the absence of a standard definition of multidirectional instability in literature 13 . Al- though all the patients are classified based on their medical history, physical examination, under anaesthesia and arthroscopic evaluations, the wide range of reported lesions indicates that the etiology of the multidirectional instability is multi-factorial and variable 14,15 . It is therefore possible that different pathologies, with different etiologies, are gathered under the same name.…”
Section: Discussionmentioning
confidence: 99%